2023
DOI: 10.1186/s12906-022-03826-4
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of the mechanism by which Huangqi Guizhi Wuwu decoction inhibits Lps-induced inflammation by regulating macrophage polarization based on network pharmacology

Abstract: Background Huangqi Guizhi Wuwu decoction (HQGZWWD) is a traditional Chinese herbal medicine formulation with significant anti-inflammatory activity. However, its underlying mechanism remains unknown. Through network pharmacology and experimental validation, this study aimed to examine the potential mechanism of HQGZWWD in regulating macrophage polarization and inflammation. Methods The active components were obtained from the Traditional Chinese Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 100 publications
0
6
0
Order By: Relevance
“…The top five scoring nodes based on degree were ALB, MMP9, TNF, HIF1A, PTGS2, IL1B, STAT3, PPARG, PTEN, BCL2, ICAM1, MAPK1, and RELA (Table 2). A review of previous studies and literature research revealed that the targets are closely related to macrophage polarization [26,27] .…”
Section: Resultsmentioning
confidence: 99%
“…The top five scoring nodes based on degree were ALB, MMP9, TNF, HIF1A, PTGS2, IL1B, STAT3, PPARG, PTEN, BCL2, ICAM1, MAPK1, and RELA (Table 2). A review of previous studies and literature research revealed that the targets are closely related to macrophage polarization [26,27] .…”
Section: Resultsmentioning
confidence: 99%
“…The MAPK signaling pathway is one of the upstream pathways of NF-κB, and phosphorylation of ERK, JNK, and p38 activates the NF-κB signaling pathway or other transcription factors [ 18 ]. NF-κB is associated with NF-κB inhibitor (IκB) binding and exists in the cytoplasm in a static state.…”
Section: Resultsmentioning
confidence: 99%
“…Network pharmacology is a multidisciplinary approach that utilizes theories from systems biology and pharmacology to investigate the mechanism of action of drugs in the treatment of diseases (Fu et al, 2021; Zhen et al, 2023). An increasing body of research has demonstrated that network pharmacology could systematically and comprehensively elucidate the mechanism of TCM in the treatment of diseases (Liang et al, 2023; Liao et al, 2023; Wang et al, 2023). However, the prototype compounds in herbs online databases used to generate compound–target maps produce false positive results.…”
Section: Introductionmentioning
confidence: 99%
“…To overcome this issue, ingredients absorbed into the bloodstream were used as target components in network pharmacologic analysis, yielding more reliable results. With the crossover of multiple disciplines and the emergence of new technologies, ultra‐performance liquid chromatography–quadrupole time‐of‐flight mass spectrometry (UPLC–Q‐TOF–MS) has been widely used in drug analysis and identification because of its advantages of high sensitivity and fast analysis speed (Ming et al, 2021; Wang et al, 2023; Zhou et al, 2021).…”
Section: Introductionmentioning
confidence: 99%